THE INFLUENCE OF PRODUCT QUALITY, PRICE AND PROMOTION ON CONSUMER LOYALTY TO LUWAK WHITE KOFFIE COFFEE PRODUCTS IN LHOKSEUMAWE CITY - Hafidh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the effect of product quality, price and promotion on consumer loyalty to luwak white coffee products in Lhokseumawe city. This study uses primary data obtained by distributing questionnaires to 100 respondents selected using the Nonprobabality Sampling technique. The data analysis method used is multiple linear regression method with the help of SPSS. Product quality (X1) partially has a positive and significant effect on consumer loyalty (Y) on luwak white coffee products in Lhokseumawe city. This shows that good product quality can foster consumer loyalty to the product, Price (X2) has a positive and significant effect on consumer loyalty (Y) on luwak white coffee products in Lhokseumawe city, and Promotion (X3) has a positive and significant effect on consumer loyalty (Y) on luwak white coffee products in Lhokseumawe city. Simultaneously, product quality (X1), product (X2) and promotion (X3) have a positive and significant effect on consumer loyalty (Y) on luwak white koffie coffee products in Lhokseumawe city